Fatigue crack growth analysis based on energy parameters: A literature review - Antunes, Fernando Ventura; Sérgio, E. R.; Moreno Cerezo, Pablo; López-Crespo, Pablo; Neto, Diogo Mariano (Elsevier, 2025)
Fatigue crack growth (FCG) in metallic materials has been studied using non-linear parameters, which permit a better understanding of crack tip damage. The objective here is to make a literature review about the use of energy parameters in this context. Fundamental concepts are presented, namely the different types of energy that can be identified (the external work, the macroscopic elastic energy, the plastic dissipation, the internal potential energy and the thermal energy). FCG rate has been related with the dissipated energy measured externally, with the dissipated energy in the reversed plastic zone, with a punctual value of dissipated density energy at a critical location ahead of crack tip and with the thermal energy. The links between FCG mechanisms and energy parameters are exploited and guidelines for their use are proposed.
Keywords: Materiales - Fatiga; Energía; Fatigue crack growth; Energy parameters; Dissipated energy; Heat generation; Thermal energy